The impact of Nepal's national incentive programme to promote safe delivery in the district of Makwanpur. - Powell-Jackson, T; Neupane, B; Tiwari, S; Tumbahangphe, K; Manandhar, D; Costello, A (2009)
OBJECTIVE: Nepal's Safe Delivery Incentive Programme (SDIP) was introduced nationwide in 2005 with the aim of encouraging greater use of professional care at childbirth. It provided cash to women giving birth in a public health facility and an incentive to the health provider for each delivery attended, either at home or in the facility. We aimed to assess the impact of the programme on neonatal mortality and health care seeking behaviour at childbirth in one district of Nepal. METHODS: Impacts were identified using an interrupted time series approach, applied to houSehold data. We estimated a model linking the level of each outcome at a point in time to the start of the programme, demographic controls, a vector of time variables and community-level fixed effects. FINDINGS: The recipients of the cash transfer in the programme's first two years were disproportionately wealthier households, reflecting existing inequality in the use of government maternity services. In places with women's groups--where information about the policy was widely disseminated--the SDIP substantially increased skilled birth attendance, but failed to impact on either neonatal mortality or the caesarean section rate. In places with no women's groups, the SDIP had no impact on utilisation outcomes or neonatal mortality. IMPLICATIONS FOR POLICY: The lack of any impact on neonatal mortality suggests that greater increases in utilisation or better quality of care are needed to improve health outcomes. The SDIP changed health care seeking behaviour only in those areas with women's groups highlighting the importance of effective communication of the policy to the wider public.